PELAKSANAAN KETERTIBAN UMUM (SUDI KASUS PASAR SIMPANG PADANG DURI) DI KECAMATAN MANDAU - Beddy, Vonni; Rusli, Zaili (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Mandau is a cross region of the various regions. Development always occurs from time. Problem often encountered is closely related to the problem of overpopulation. Mandau is a rapid development of the business sector infrastructure even in this area is growing so rapidly that it becomes the target sector to creat jobs the informal sector, which vendors are selling. If look to major roads that are often ecountered are vendors who sell to on the road and there is congestion and disrupt traffic behaviour. But in regulating this issue saber subdistrict goverment should have a policy for the implementation of public order by executing the task by Police Unit of Pamong Praja. In the medel implementations by Van Meter and Van Horn, there are six variables that shape the relationship between policies and performance, namely : basic measures and policy objectives, policy resources, inter-organizational communication and implementation activities, the characteristics of the implementaters, economic conditions, social and political trends executor. The reseach method used in this study is a qualitative research, with techniques that are done of snowball sampling, the key informants in this study. The informant who conducted the interview was from Police Unit of Pamong Praja Mandau and fiber UPTD police civil service departements and hygiene market, the analyze the data and manage the data. Based on the research that has been done, and based on the theoritical concept. Implementation of public order (Market case study intersections desert thorn Mandau) in the district mandau. Basically been carried out by the Police Unit of Pamong Praja and UPTD Departement and Hygiene Market. But never be running with a constant order, the hawkers back peddle. Do not have a clear sanction any mistakes made by vendors that posed on deterrent properties. Goverment also did not pay attention to the problem pf street vendors with deep. So it happened so long and prottacted. Plus the absence of a clear warning to the o authorized organization itself.Keyword: Public Order, Implementation, Street Vendors